2013
DOI: 10.1007/s00330-013-3083-8
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body MRI with diffusion-weighted sequence for staging of patients with suspected ovarian cancer: a clinical feasibility study in comparison to CT and FDG-PET/CT

Abstract: • Whole-body MRI with diffusion weighting (WB-DWI/MRI) helps to assess the operability of suspected ovarian cancer. • Interobserver agreement is good for primary tumour characterisation, peritoneal and distant staging. • WB-DWI/MRI improves mesenteric/serosal metastatic spread assessment compared with CT and FDG-PET/CT. • Retroperitoneal/cervical-thoracic nodal staging using qualitative DWI criteria was reasonably accurate. • WB-DWI/MRI and FDG-PET/CT showed the highest diagnostic impact for detecting thoracic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
155
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(169 citation statements)
references
References 46 publications
4
155
1
9
Order By: Relevance
“…With simultaneous PET/MR imaging being a novel technique, few studies have investigated it. Comparing the diagnostic accuracy of whole-body DWI and MR imaging with that of PET/CT for tumor staging, Michielsen et al reported an equivalent diagnostic accuracy for characterization of primary ovarian cancers and detection of lymph nodes and distant metastases yet also revealed the superiority of DWI and MR imaging for detecting and characterizing peritoneal lesions (9). Similar results were shown by Soussan et al, who found that DWI and MR imaging are superior to PET/CT for detecting peritoneal implants in the right supramesocolic area (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With simultaneous PET/MR imaging being a novel technique, few studies have investigated it. Comparing the diagnostic accuracy of whole-body DWI and MR imaging with that of PET/CT for tumor staging, Michielsen et al reported an equivalent diagnostic accuracy for characterization of primary ovarian cancers and detection of lymph nodes and distant metastases yet also revealed the superiority of DWI and MR imaging for detecting and characterizing peritoneal lesions (9). Similar results were shown by Soussan et al, who found that DWI and MR imaging are superior to PET/CT for detecting peritoneal implants in the right supramesocolic area (7).…”
Section: Discussionmentioning
confidence: 99%
“…The use of integrated PET/CT has become well established within the last decade for whole-body staging in oncologic patients (6). Various studies investigating the diagnostic capacity of DWI or MR imaging and of PET/CT have reported comparable results for detection and characterization of tumors, including gynecologic malignancies (7)(8)(9).…”
mentioning
confidence: 99%
“…Diagnostic imaging is used to determine the suitability of the patient for surgery by assessing the primary tumor or by describing the disease volume and extent (7,8). DWI, as a functional MRI technique, provides non-invasive and high-resolution information on tissue characteristics based on molecular water diffusion properties, and the imaging output is useful to determine tissue microstructure, density, microcirculation and cellular organization (9,11,33). Several studies describe a close association between cell density and ADC values (16,(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion weighted imaging (DWI) is a non-invasive technique based on molecular water diffusion properties, and may be used to characterize tissue architecture based on microstructure, cellular density, microcirculation and cell organization (9)(10)(11). DWI has been demonstrated to be more accurate compared with computed tomography (CT) for characterizing the sites of implants of ovarian cancers, including metastases to the liver, lungs, kidneys, uterus and pancreas (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, any other extra-abdominal localization as well as abdominal intraparenchymal and retroperitoneal metastases cannot be assessed. The value of this approach consists in the fact that a) most AEOC cases have trans-celomatic diffusion, which is the key point for surgical debulking and finally prognosis, b) standard imaging techniques have a high false negative rate in term of intraperitoneal staging [4].…”
Section: First Perspectivementioning
confidence: 99%